Luis Bunuel: el fantasma de la libertad entre el instinto y la risa (Significação: Journal of Audiovisual Culture, 2008)
Bufiuel's themes are familiar to us, but what is important in his films is how he presents these themes as a mixture of the rational and the irrational. For the Spanish director film is an instrument of poetry and, in this sense, he develops writing modalities to express ali kind of liberating significations. In the article the author explores one of these manners of cinematographic writing.